The Effects of Mindfulness Training and TikTok Content Characteristics on Students’ Learning Motivation, Classroom Behavior, and Academic Performance - Gilbert Leonardo Devincie (The Eastasouth Journal of Learning and Educations, 2026)
This study examines how mindfulness training and TikTok content characteristics influence students' learning motivation, classroom behavior, and academic performance at Universitas Bunda Mulia. Using a quantitative explanatory survey combined with a quasi-experimental one-group pre-test and post-test design, the study involved 120 active students who regularly used TikTok and joined a four-week mindfulness program. Data were collected through structured questionnaires, classroom observation sheets, and course-grade documentation, then analyzed using descriptive statistics, multiple regression, paired-sample t-test, and moderation analysis. The findings show that mindfulness training improved students' focus, classroom engagement, and academic performance. TikTok content characteristics, especially information quality, credibility, attractiveness, and interactivity, also positively influenced learning motivation. Moreover, mindfulness strengthened the relationship between educational TikTok content and learning motivation by helping students regulate attention and filter distracting content. These results suggest that higher education institutions should combine mindful learning practices, digital literacy, and credible short-video learning resources to support students' motivation and academic success.This study examines how mindfulness training and TikTok content characteristics influence students' learning motivation, classroom behavior, and academic performance at Universitas Bunda Mulia. Using a quantitative explanatory survey combined with a quasi-experimental one-group pre-test and post-test design, the study involved 120 active students who regularly used TikTok and joined a four-week mindfulness program. Data were collected through structured questionnaires, classroom observation sheets, and course-grade documentation, then analyzed using descriptive statistics, multiple regression, paired-sample t-test, and moderation analysis. The findings show that mindfulness training improved students' focus, classroom engagement, and academic performance. TikTok content characteristics, especially information quality, credibility, attractiveness, and interactivity, also positively influenced learning motivation. Moreover, mindfulness strengthened the relationship between educational TikTok content and learning motivation by helping students regulate attention and filter distracting content. These results suggest that higher education institutions should combine mindful learning practices, digital literacy, and credible short-video learning resources to support students' motivation and academic success.